Unmanaged Transparency in a Digital Society: Swiss army knife or double-edged sword?. Issue 1 (January 2023) - Reischauer, Georg; Ringel, Leopold
Facing increasing demands for transparency, more and more organizations have embraced managed forms of information disclosure that rely on digital technologies. However, when doing so, they tend to create an idealized self-presentation for their audiences. Aggravated by these attempts to undermine 'true openness', calls for a 'hands-off' approach to information disclosure – also known as unmanaged transparency – have grown louder. Following this development, the paper conceptualizes organizations as sites of managed and unmanaged transparency practices and asks how these practices shape audience support and are affected by audiences. Empirically, we study a German political party from 2011 to 2017. Audiences initially supported the party's commitment to unmanaged transparency but soon withdrew their support. Members in executive positions reacted by enacting multiple managed transparency practices to change the party's negative public image. These efforts, however, were futile, and the party could not regain audience support. We theorize this dynamic in a framework that draws attention to the impact of (un)managed transparency and the organizational environment on audience support. Overall, our study suggests that unmanaged transparency in a digital society is more like a double-edged sword rather than a Swiss army knife: organizations might profit from its positive effects on the audience's support, but they also make themselves vulnerable by the high level of dissonance they put on display.